Intensitas Puasa Senin Kamis terhadap Kematangan Emosi Remaja Putri: Studi di Lembaga Kesejahteraan Sosial Anak Taman Harapan Muhammadiyah Kota Bandung - Khoiriyah, Nurul; Muaz, Abdul; Atamimi, Abdul Basit (Journal of Sufism and Psychotherapy, 2023)
During adolescence, a person will generally experience changes both socially, psychologically and hormonally. These changes can influence behavior that is difficult to understand and this period is often referred to as a period full of difficulties. Efforts to train emotional maturity in teenagers can be done by fasting, one of which is the sunnah fast on Mondays and Thursdays. Therefore, this article aims to determine the effect of the intensity of Monday and Thursday fasting on the emotional maturity of young women at LKSA Taman Harapan Muhammadiyah, Bandung City. The research method used is a combined type of research between qualitative and quantitative. The population in this study as a whole used as a sample for this research was orphaned and underprivileged teenage girls at middle and high school levels, totaling 35 foster teenage girls. The primary data source in this research is the young women of LKSA Taman Harapan Muhammadiyah Bandung City from grades 1-3 of middle school and high school. Secondary data sources for this research are books, journals, previous theses, official documentation and institutional administrative data. The aim of this research was to determine the intensity of Monday and Thursday fasting on the emotional maturity of young women at LKSA Taman Harapan Muhammadiyah, Bandung City. The results obtained state that there are changes in emotional maturity including self-understanding in adolescents, but not overall changes can be experienced because there are still some of the respondents who are still not consistent in fasting on Mondays and Thursdays.